Correlation between energy and displacement demands for infilled reinforced concrete frames - Angelucci, G.; Mollaioli, F.; Quaranta, G. (Frontiers in Built Environment, 2023)
It is well recognized that masonry infills, even though they are non-structural elements, might offer a significant earthquake resistance and can prevent the collapse of relatively weak reinforced concrete structures. The goal of this study is to investigate the energy dissipation contribution of masonry infills in reinforced concrete frames subjected to earthquake ground motion. To this purpose, a stick-type model with and without infills is considered for the evaluation of the inelastic response of representative frame structures. The infills are modeled by means of equivalent strut elements, which can only carry compressive loads. To investigate the influence of their mechanical characteristics, different idealized type of masonry infills are considered, and the weakest one is selected for the dynamic analyses based on the whole strong motions database. Wide ranges of structural systems and natural periods are taken into account, in such a way to establish response spectra for several significant parameters, including those based on energy. The results of the present investigation demonstrate that the infills significantly contribute to the energy dissipation capacity, provided that they are present in all stories. It is found that the contribution of masonry infills is of great importance in reducing both dissipation and displacement energy demands in frame elements. The effectiveness of their contribution depends on the characteristics of the ground motion, especially for non-seismic frames.